PREVENTION AND ERADICATION OF DRUG TRAFFICKING IN INDONESIA - Endeh Suhartini; Martin Roestamy; Ani Yumarni (UNTAG Law Review, 2018)
Many countries including Indonesia have concerned about the increase of drug trafficking. Currently Indonesia has been in the situation where there is an “Emergency on Drugs Trafficking”. Lot of efforts to solve and prevent the growth of drug trafficking has been done to save young generation. Criminal Acts on Drugs which have been spread out need to be cut off because the drug trafficking has happened nationally and even has crossed international boundaries.The Aims of this research are to identify and analyses necessary actions to prevent and solve the drug trafficking. Then, to find an ultimate solution in handling arising obstacles within such prevention and eradication of drug trafficking in Indonesia.This research uses a juridical normative approach method which reviews theories, concepts, legal principals, and prevailing rules and regulations. Moreover, it also applies an empirical approach as supporting study to gain more factual data.In conclusion, illegal drug trafficking has become both national and international social issue and even a legal issue in society. Certain legal actions are required to take to prevent and solve the drug trafficking in Indonesia, which one of them is by rules and regulations. Law Number 35 of 2009 regarding Drugs is a legal basis for the prevention and eradication of drug trafficking in Indonesia.The research limitation is focus on increasing and preventing drugs should be supported by all parties of the family, community and government.Drugs is an international and national case that is difficult to overcome considering their networks are hidden and require special skills where necessary national and international cooperation so that drug circulation can be overcome quickly